Particulate Organic Matter Distributions in the Water Column of the Chukchi Sea During Late Summer. Issue 9 (14th September 2021) - Goñi, Miguel A.; Juranek, Lauren W.; Sipler, Rachel E.; Welch, Kylie A.
Abstract: Two oceanographic cruises were completed in September 2016 and August 2017 to investigate the distribution of particulate organic matter (POM) across the northeast Chukchi Shelf. Both periods were characterized by highly stratified conditions, with major contrasts in the distribution of regional water masses that impacted POM distributions. Overall, surface waters were characterized by low chlorophyll fluorescence (Chl Fl < 0.8 mg m −3 ) and particle beam attenuation ( c p  < 0.3 m −1 ) values, and low concentrations of particulate organic carbon (POC < 8 mmol m −3 ), chlorophyll and pheophytin (Chl + Pheo < 0.8 mg m −3 ), and suspended particulate matter (SPM ∼2 g m −3 ). Elevated Chl Fl and Chl + Pheo (∼2 mg m −3 ) values measured at mid‐depths below the pycnocline defined the subsurface chlorophyll maxima (SCM), which exhibited moderate POC (∼10 mmol m −3 ), c p (∼0.4 m −1 ) and SPM (∼3 g m −3 ). In contrast, deeper waters below the pycnocline were characterized by low Chl Fl and Chl + Pheo (∼0.7 mg m −3 ), high c p (>1.5 m −1 ) and SPM (>8 g m −3 ) and elevated POC (>10 mmol m −3 ). POM compositions from surface and SCM regions of the water column were consistent with contributions from active phytoplankton sources whereas samples from bottom waters were characterized by high Pheo/(Chl + Pheo) ratios (>0.4) indicative of altered phytoplankton detritus. Marked contrasts in POM were observed in both surface and middepth waters during both cruises. Increases in chlorophyll and POC consistent with enhanced productivity were measured in middepth waters during the September 2016 cruise following a period of downwelling‐favorable winds, and in surface waters during the August 2017 cruise following a period of upwelling‐favorable winds. Plain Language Summary: We investigated the distribution and composition of particulate organic matter in waters from the northeast Chukchi Sea during two late summer periods (September 2016 and August 2017). During both cruises we measured a variety of properties (salinity, temperature, density, chlorophyll fluorescence and particle beam attenuation). We also collected individual water samples from specific depths and measured the concentrations of suspended particulate matter, particulate organic carbon and nitrogen, chlorophyll‐a and pheophytin (a chlorophyll degradation product). These measurements revealed highly stratified conditions throughout the study area, with surface waters exhibiting relatively low particle and biomass concentrations, middepth waters with well‐defined subsurface chlorophyll maxima and moderate biomass, and turbid bottom waters with intermediate concentrations of particulate organic carbon and elevated levels of pheophytin. Large contrasts in the composition of particulate materials in both cruises were related to the distribution of different regional water masses. In addition, we observed increases in biogeochemical tracers of phytoplankton production in response to downwelling‐ and upwelling‐favorable wind events. Overall, our work suggests that under the right conditions, phytoplankton production may occur under highly stratified conditions both in surface and sub‐surface waters, extending the productive season along Arctic marginal seas. Key Points: There are marked contrasts in particulate organic matter (POM) distributions and compositions associated with distinct water masses on the northeast Chukchi Shelf Despite high stratification, wind events elicit increases of plankton‐derived POM in subsurface regions of the water column Turbid bottom waters display elevated concentrations of mineral‐rich particles enriched in altered POM likely resuspended from the seabed